2014
DOI: 10.1016/j.fishres.2014.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale distribution of three deep-water squaloid sharks: Integrating data on sex, maturity and environment

Abstract: Deep-water sharks exhibit species-specific reproductive strategies, which include segregation by sex, size and reproductive stage. However, due to the wide spatial distribution of most species, available information, usually collected at a regional scale, is usually not adequate to infer species reproductive spatial dynamics. This study draws together information on the distribution of reproductive stages of three species of squaliform sharks: Portuguese dogfish Centroscymnus coelolepis (Somniosidae), leafscal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 38 publications
1
38
0
Order By: Relevance
“…(Castro, 2011;Compagno, 1984;McLaughlin and Morrissey, 2004;Russell et al, 1988). Capture depths for S. cubensis ranged from 472.6 m -730.6 m, far greater than the 60 m -380 m previously reported by Compagno (1984), the slightly increased range of 110 m -500 m reported by Castro (2011) or the 50 m to 459 m reported by Jones et al (2014). This variation in depth association is Expanded depth ranges were also found for H. nakamurai, a species thought to inhabit the deep continental slope and have a circumglobal distribution .…”
Section: Resilience To Longline Capturementioning
confidence: 50%
See 1 more Smart Citation
“…(Castro, 2011;Compagno, 1984;McLaughlin and Morrissey, 2004;Russell et al, 1988). Capture depths for S. cubensis ranged from 472.6 m -730.6 m, far greater than the 60 m -380 m previously reported by Compagno (1984), the slightly increased range of 110 m -500 m reported by Castro (2011) or the 50 m to 459 m reported by Jones et al (2014). This variation in depth association is Expanded depth ranges were also found for H. nakamurai, a species thought to inhabit the deep continental slope and have a circumglobal distribution .…”
Section: Resilience To Longline Capturementioning
confidence: 50%
“…complex and H. nakamurai were the significantly skewed sex ratios. Demographic segregation is considered normal for many populations of shallow water elasmobranchs (Mucientes et al, 2009;Springer, 1967;Speed et al, 2012), and has also been reported in many deep-water species (Girard and Du Buit, 1999;Moura et al, 2014 Squalus cubensis has previously been reported to form large schools stratified by size and sex (Castro, 2011), and it is interesting to note that Daly-Engel et al (2010) reported strong sexual segregation in a congener, Squalus cf. mitsukurii.…”
Section: Resilience To Longline Capturementioning
confidence: 86%
“…), and one small individual of 33·0 cm L T was recorded in this study on Chatham Rise, suggesting O. bruniensis may pup in multiple locations around New Zealand. Immature individuals have been previously reported at depths deeper than adults (Moura et al, ), however, in the case of O. bruniensis, any small individuals would still occur within the range of commercial and research trawls, and should have been detected. The presence of young O. centrina specimens in coastal waters suggests inshore mating and pupping areas (Capapé et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…McCulloch 1915 Daley et al (2002), but four of the 2711 specimens reported by Moura et al (2014) were longer (1260, 1360, 1420 and 1620 mm; all females) and among 420 specimens examined by Rochowski et al (2015), the largest female was 1530 mm 376 Deania hystricosa (Garman 1906 Bigelow & Schroeder (1948). Maximum sizes of 315 mm precaudal length (Longley & Hildebrand, 1941) and 500 mm L T (Compagno, 1984a) probably refer to the subsequently described and very similar E. robinsi, which attains a greater maximum size according to Schofield & Burgess (1997).…”
Section: Centrophorus Harrissonimentioning
confidence: 99%